2014
DOI: 10.3109/01443615.2014.991297
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of human chaperonin 10 and high-sensitivity C-reactive protein levels of infertile women who underwent ovulation induction and intra-uterine insemination

Abstract: The implantation of embryo is one of the crucial steps of a successful pregnancy. The foetus should be protected from maternal immune system, for the appropriate implantation and modification in maternal immunity is crucial. We investigated high-sensitivity C-reactive protein (hs CRP), which is an indicator of low-grade inflammation and Cp10 that has immunosuppressant and growth-promoting capabilities at embryo levels in ovulation induction and intra-uterine insemination (IUI)applied in infertile women. The ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, the group that achieved pregnancy was significantly younger on average (25.5 ± 5.4 vs. 29.2 ± 5.4 years, P =.012), which was not adjusted for in the analysis ( 21 ). Another similar study compared the hs-CRP levels 2 and 8 days after IUI and found no difference between pregnant and non-pregnant patients, but this study was limited by its small sample size (n = 42), and only 8 patients became pregnant ( 22 ).…”
Section: Discussionmentioning
confidence: 91%
“…However, the group that achieved pregnancy was significantly younger on average (25.5 ± 5.4 vs. 29.2 ± 5.4 years, P =.012), which was not adjusted for in the analysis ( 21 ). Another similar study compared the hs-CRP levels 2 and 8 days after IUI and found no difference between pregnant and non-pregnant patients, but this study was limited by its small sample size (n = 42), and only 8 patients became pregnant ( 22 ).…”
Section: Discussionmentioning
confidence: 91%
“…these changes may affect the success rate of IVF/ICSI, implantation, and pregnancy, also adminstration of human chorionic gondotropin (HCG) regardless of the response rate of the ovaries, causes activation of endothelial cells and neutrophils. [7][8][9] The level of CRP increases in ovulation stimulation cycle with standard long protocol. Wunder et al in 2005 showed that leptin and CRP in ovulation stimulation cycle increase until the day of puncture, 9 Orvieto et al showed the same results.…”
Section: Resultsmentioning
confidence: 99%